(untitled) (UUM Journal of Legal Studies, 2024)
Over the past 12 years, the escalation of violence in conflicts arising from disputes over natural resource management rights between corporations and indigenous communities has become a growing concern across all regions of Indonesia. This abstract introduction highlights the urgent need to address the rising tensions and clashes associated with the competing claims to and utilization of natural resources in the country. Therefore, this study aimed to analyse the causes of violence and conflict resolution over natural resources using an empirical legal study with a socio-legal approach adopted through a case study in Bengkulu Province, Indonesia. Informants for the study were selected using a snowball sampling technique, ensuring a diverse and representative range of perspectives. Secondary data was obtained through a literature study by tracing information from journals, books, and the internet, and data analysis was carried out qualitatively. Furthermore, an analysis was performed on the findings of other studies concerning instances of violence in conflicts related to forest and mining resources. This research found that (1). The violence occurred because the company did not respect the customary community’s natural resource control rights. (2). However, violence can be stopped through violence or mediation (3). Resolution of violence in conflict can only be done through mediation. The authors recommend that: (1). The practice of resolving violence in conflicts of rights over natural resources through mediation needs to be strengthened by the government to realize justice for all. (2). In indigenous communities, apart from state law, the legal landscape is still heavily influenced by customary law and religious law.